2016
DOI: 10.1038/srep22342
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of fluorescent protein brightness on protein concentration in solution and enhancement of it

Abstract: Fluorescent proteins have been widely used in biology because of their compatibility and varied applications in living specimens. Fluorescent proteins are often undesirably sensitive to intracellular conditions such as pH and ion concentration, generating considerable issues at times. However, harnessing these intrinsic sensitivities can help develop functional probes. In this study, we found that the fluorescence of yellow fluorescent protein (YFP) depends on the protein concentration in the solution and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 62 publications
2
59
0
Order By: Relevance
“…Other sensors have been developed, including a synthetic sensor based on polyethylene glycol that is compressed by macromolecular crowding (15), and a genetically encoded sensor that is based on protein-induced destabilization of an impaired YFP (16). The polyethylene glycol 10,000 (PEG)-based sensor may function via a similar mechanism to our sensor, whereas the mechanism behind the destabilization of the YFP sensor is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Other sensors have been developed, including a synthetic sensor based on polyethylene glycol that is compressed by macromolecular crowding (15), and a genetically encoded sensor that is based on protein-induced destabilization of an impaired YFP (16). The polyethylene glycol 10,000 (PEG)-based sensor may function via a similar mechanism to our sensor, whereas the mechanism behind the destabilization of the YFP sensor is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, in vitro calibrations may not fully recapitulate the sensor behavior in cells, considering that its signal can be affected by the cellular environment (Dittmer, Miranda, Gorski, & Palmer, 2009). For example, genetically encoded, engineered protein sensors can be sensitive to molecular crowding (Dittmer et al, 2009;Morikawa et al, 2016), which is a major distinction between the purified protein and the in-cell calibrations.…”
Section: (B) (A)mentioning
confidence: 99%
“…4A). Recently, Morikawa et al found that the fluorophore of YFP is sensitive to protein crowding (Morikawa et al, 2016). They introduced a mutation to increase the sensitivity to the protein crowding and generated a proteincrowding sensor (Fig.…”
Section: Fret Biosensors Based On the Intrinsic Properties Of Fluoresmentioning
confidence: 99%